Innovation of Pedagogical Practices of Future Teachers - Petra Konečná; Pavel Smolka; Kateřina Trčková; Zuzana Václavíková; Martin Žáček (MDPI AG, 2023)
The basic topic of this article is the undergraduate preparation of future teachers in the Czech Republic, specifically the issue of the pedagogical practices of future teachers. We focused mainly on reflective activities within this preparation. The first part of the article deals with the mapping of this area in the educational systems of other countries or other regions of the Czech Republic. The second part is devoted to a description of the current state of reflection among science teacher education students. It also proposes an innovation of the system of reflection implementation using modern IT tools in the context of full-time and distance education. The third part presents the outputs of the e-questionnaire prepared for both face-to-face and distance learning.